Paradojas de la sujeción social - Hernán Sosa, Carlos (Verba hispanica, 2013)
The article analyses the way in which the ever-present theme of the bourgeois marriage in the narrative works of the Argentinean writer Roberto Arlt also features in his short story Noche terrible and in less pronounced form in other accounts included in the volume El Jorobadito. Through a detailed analysis of the discourse representation of the moral and social alienation which the lead character of Noche terrible experiences on the eve of his marriage,it is possible to reconstruct the wearisome processes by which, in the narrative of Roberto Arlt, the cogs of society subordinate individuals and thus preventany from escaping from inexorable class constraints.
Keywords: Arlt, Roberto, 1900-1942; argentinska književnost; Arlt, Roberto: Noche terrible; Arlt, Roberto: El Jorobadito; 20.st.; kratka proza